Effects of Drying Temperature on Bioactive Compounds Retention in Dragon Fruit (Hylocereus undatus) Peel Powder - Gautam, Navin; Basyal, Bhawana; Bhattarai, Kabindra (Himalayan Journal of Science and Technology, 2024)
The dragon fruit peels are discarded despite the high content of bioactive components such as phenolic, flavonoid, betacyanin content, and antioxidant activity. Drying these peels to powder for use as an infusion might aid in its valorization. Therefore, this study aimed to assess effects of drying peels at three different temperatures (50°C, 60°C, and 70°C) on retention of bioactive compounds in the resulting powder. For this, dragon fruit peels were cut into 2.5 cm length and 3.0-3.5 mm thickness and dried at three temperatures until the moisture content reached around 5%. Then the dried peels were ground, and sieved through a 40-mesh size screen. Proximate analysis and bioactive components were determined for fresh and dried dragon peel powder prepared for infusion. A sensory evaluation of infusion was conducted by steeping 1.5 g of dried dragon fruit peel in 50 ml of hot water (90°C) for 5 min, using a 9-point hedonic scale. The results showed that peel dried at 50°C retained significantly higher amounts of bioactive compounds with a total polyphenol content of 64.9 mg GAE/100g extract, total flavonoid content of 56.34 mg QE/100 g extract, and betacyanin content of 52.34 μg/100 g dry matter extract. Moreover, the extract of peel powder dried at 50°C exhibited 77.37% DPPH radical scavenging activity at a concentration of 2.8 mg/ml. In addition, sensory panelist significantly preferred the infusion prepared from the peels dried at 50°C to those dried at other temperatures. This study suggests that processing dragon fruit peels into powder for infusion preparation is a viable strategy to reuse peels that would typically be discarded.